2023
DOI: 10.3390/ijms241613013
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Kinetic Parameters and Identification of the Rate-Determining Steps in the Oxygen Exchange Process for LaNi0.6Fe0.4O3−δ

Natalia Porotnikova,
Dmitriy Zakharov,
Anna Khodimchuk
et al.

Abstract: The mixed ionic and electronic oxide LaNi0.6Fe0.4O3−δ (LNF) is a promising ceramic cathode material for solid oxide fuel cells. Since the reaction rate of oxygen interaction with the cathode material is extremely important, the present work considers the oxygen exchange mechanism between O2 and LNF oxide. The kinetic dependence of the oxygen/oxide interaction has been determined by two isotopic methods using 18O-labelled oxygen. The application of the isotope exchange with the gas phase equilibrium (IE-GPE) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…SrFeO 3−δ -based materials are the most widely studied for cathodes in iron-based systems. Other researchers have shown that the structure of SrFeO 3−δ varies significantly with the temperature and oxygen partial pressure [24][25][26][27][28][29][30][31][32][33][34][35][36]. Jiang et al introduced high-valence Nb into Fe and found that the modification of Nb enhanced the stability of the crystal and effectively avoided the phase transition.…”
Section: Introductionmentioning
confidence: 99%
“…SrFeO 3−δ -based materials are the most widely studied for cathodes in iron-based systems. Other researchers have shown that the structure of SrFeO 3−δ varies significantly with the temperature and oxygen partial pressure [24][25][26][27][28][29][30][31][32][33][34][35][36]. Jiang et al introduced high-valence Nb into Fe and found that the modification of Nb enhanced the stability of the crystal and effectively avoided the phase transition.…”
Section: Introductionmentioning
confidence: 99%